2014
DOI: 10.2147/ccid.s60313
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric facial skin viscoelasticity during climacteric aging

Abstract: BackgroundClimacteric skin aging affects certain biophysical characteristics of facial skin. The purpose of the present study was to assess the symmetric involvement of the cheeks in this stage of the aging process.MethodsSkin viscoelasticity was compared on both cheeks in premenopausal and post-menopausal women with indoor occupational activities somewhat limiting the influence of chronic sun exposure. Eighty-four healthy women comprising 36 premenopausal women and 48 early post-menopausal women off hormone r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The image analysis of wrinkles at the localized sites was only performed on the left side of the face. Hence, there may have been under‐ or overestimation of the amount of wrinkles due to asymmetry in facial photoaging . However, at a population level it probably does not radically influence the results.…”
Section: Discussionmentioning
confidence: 99%
“…The image analysis of wrinkles at the localized sites was only performed on the left side of the face. Hence, there may have been under‐ or overestimation of the amount of wrinkles due to asymmetry in facial photoaging . However, at a population level it probably does not radically influence the results.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated that skin viscoelasticity values obtained by cutometer, which indicate the biomechanical properties of the skin, decreases with age [32][33][34]. Furthermore, photo aged dermis contains significantly reduced levels of collagen types I and III, fewer anchoring fibrils at the Dermal-Epidermal Junction (DEJ; collagen VII) and loss of the fibrillin-rich microfibrillar architecture in the papillary dermis [35].…”
Section: Discussionmentioning
confidence: 99%
“…Sex may influence the factors analyzed here, as middle-aged women can be affected by asymmetric facial skin viscoelasticity after menopause due to hormonal changes. 30 Additional prospective studies are needed to further evaluate the relationships among lip-line cant, aging, and the craniofacial complex using a homogenous sample.…”
Section: Discussionmentioning
confidence: 99%